Strategies for Instilling Muhammadiyah Values within the Faculty of Islamic Religion, University of Muhammadiyah Palu - Eka Firmansyah; Nurhakim Nurhakim (International Journal of Health, Economics, and Social Sciences (IJHESS), 2022)
In instilling the values ​​of kemuhammadiyahan to others, it is certainly not an easy process, in creating a society that recognizes and also practices the values ​​of kemuhammadiyahn requires a good way or strategy so that what is given to the community can be understood or understood properly. This article discusses strategies for instilling muhammadiyahan values ​​within the Faculty of Islamic Religion, University of Muhammadiyah Palu. which, as the results of our research, found several strategies, such as the inclusion of AIK courses in learning, also holding monthly recitations that discussed kemuhammadiyahan, as well as incorporating kemuhammadiyahan materials into the cadre of organizations of the Faculty of Islamic Religion. And briefly, we convey that the strategy being pursued is very effective and also successful. This can be seen from the quality and insight of the Muhammadiyah in each element within the Faculty of Islamic Religion, as well as the birth of many new Muhammadiyah cadres from the cadre process carried out by organizations within the Faculty of Islamic Religion. In this study, the author uses a naturalistic paradigm, with a qualitative type of research, and with a case study approach.